2010
DOI: 10.1063/1.3466659
|View full text |Cite
|
Sign up to set email alerts
|

Vortex dynamics in a wire-disturbed cylinder wake

Abstract: The effect of a thin control wire on the wake properties of the flow around a circular cylinder has been investigated numerically. The governing equations are solved using a spectral element method for a Reynolds number of ReD=100. The diameter ratio of the main cylinder and the wire equals D/d=50 so no vortex shedding is expected to occur for the wire. However, the vorticity introduced by the wire in the vicinity of the upper shear layer of the cylinder still affects the vortex dynamics in the wake of the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…The configuration at low Reynolds numbers was further studied by Mittal & Raghuvanshi (2001), Dipankar, Sengupta & Talla (2007), Kuo, Chiou & Chen (2007) and Marquet, Sipp & Jacquin (2008). Yildirim, Rindt & van Steenhoven (2010) studied the effect of a thin control wire on the wake properties for laminar two-dimensional wake flow, investigating its vortex dynamics and vortex shedding process. Zhang et al (1995) studied the influence of the presence of a wire in the vicinity of a cylinder on transition, also the focus of the present study, and characterized the wake transition regime as mode C, which shows different properties compared to modes A and B.…”
Section: Introductionmentioning
confidence: 99%
“…The configuration at low Reynolds numbers was further studied by Mittal & Raghuvanshi (2001), Dipankar, Sengupta & Talla (2007), Kuo, Chiou & Chen (2007) and Marquet, Sipp & Jacquin (2008). Yildirim, Rindt & van Steenhoven (2010) studied the effect of a thin control wire on the wake properties for laminar two-dimensional wake flow, investigating its vortex dynamics and vortex shedding process. Zhang et al (1995) studied the influence of the presence of a wire in the vicinity of a cylinder on transition, also the focus of the present study, and characterized the wake transition regime as mode C, which shows different properties compared to modes A and B.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, similar results have been obtained from direct numerical simulation 2,3 and global stability analysis 4 of the two-cylinder system performed at about the same Reynolds numbers. The effect upon aerodynamic forces has been studied experimentally and numerically by Dalton, Xu, and Owen 5 and Yildirim, Rindt, and Steenhoven, 6 who report reduction of the time-averaged mean drag and of the fluctuating lift, as well as enhancement of the mean lift at larger but still moderate Reynolds numbers ranging from 100 to 3000. Experimentally, the control cylinder technique has proven successful up to high, turbulent Reynolds numbers of order 10 4 -10 5 ; see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…As an illustration, Dalton et al 5 fix the gap distance separating the centers of the two cylinders to 1.4 diameters of the main cylinder, then vary only the angle of attack (that is, the angle between the center-to-center line and the free stream direction) and report a maximum drag reduction by 33% in flow past a circular cylinder at Re = 100. For the exact same flow case, Yildirim et al 6 fix the stream-wise position of the control cylinder to 0.75 diameter of the main cylinder, then vary only its cross-wise position and report a maximum drag reduction by only 6.5%. The discrepancy of course arises from both groups of authors having spanned different near-wake regions, and motivates the development of more systematical approaches relying on theoretical analysis to map quickly the best positions for placement of the control cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…The subharmonic frequency f 1 is associated with the formation of secondary vortices and points to the period-doubling character of the Mode-C transition since f 1 ≈ f 0 /2. 25 It is possible to calculate the energy content of Mode-C wake at particular frequencies by integrating the energy spectrum curve. [26][27][28] For that purpose the energy intensity e at a point in the flow field is defined as 26…”
Section: Energy Content Of the Mode-c Wakementioning
confidence: 99%
“…It is also shown that the shedding frequency in Mode-C transition is lower than the Mode-A and Mode-B frequencies for the non-wired cylinder in the same Reynolds number range. Yildirim et al 19 investigated the laminar two-dimensional wake flow for the wired-cylinder case, investigating its vortex dynamics and vortex shedding process. Furthermore, Parezanovic and Cadot 20,21 characterized the modification of a two-dimensional wake by a smaller cylinder using sensitivity maps.…”
Section: Introductionmentioning
confidence: 99%